2014
DOI: 10.1074/jbc.m113.506428
|View full text |Cite
|
Sign up to set email alerts
|

The c-FLIPL Cleavage Product p43FLIP Promotes Activation of Extracellular Signal-regulated Kinase (ERK), Nuclear Factor κB (NF-κB), and Caspase-8 and T Cell Survival

Abstract: Background: c-FLIP L is a regulator of caspase-8 activity in T lymphocytes. Results: Caspase-8 activity is lost upon deletion of c-FLIP L . p43FLIP rescues caspase-8 activity through Raf1, TRAF2, and RIPK1 association, augmenting ERK and NF-B pathways. Conclusion:The FLIP L cleavage product p43FLIP promotes activation of pathways involved with T cell growth. Significance: This study provides new insight into the regulation of caspase-8 activity by c-FLIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…In addition to controlling cell-extrinsic death, caspase-8 also plays a role in NF-κB signaling and gene expression (31,32,38,39), potentially via cleavage of cFLIP (40,41). However, YopJinduced caspase-1 activation and cell death via caspase-8 and FADD are independent of LPS-induced priming, because they are triggered by NF-κB inhibition and are independent of ASC, NLRP3, and IFNAR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to controlling cell-extrinsic death, caspase-8 also plays a role in NF-κB signaling and gene expression (31,32,38,39), potentially via cleavage of cFLIP (40,41). However, YopJinduced caspase-1 activation and cell death via caspase-8 and FADD are independent of LPS-induced priming, because they are triggered by NF-κB inhibition and are independent of ASC, NLRP3, and IFNAR.…”
Section: Discussionmentioning
confidence: 99%
“…cFLIP L was initially shown to have an inhibitory role in CD95-induced NF-κB activation (34, 121), but it was later demonstrated that it is the c-terminal domain of cFLIP L that inhibits the interaction between the DD of RIPK1 and the prodomain of caspase-8 that is required for CD95-induced NF-κB activation (122). Processing of full-length cFLIP L to p43/p22 by caspase-8 in the FADD-caspase-8-cFLIP L complex mediates NF-κB activation (123) by allowing cFLIP L p43 to interact with TRAF2 (124), RIPK1 and the IKK complex. Furthermore, the p22 fragment of processed cFLIP L was shown to be able to induce NF-κB activation by interacting with NEMO in the IKK complex (125).…”
Section: Non-cell Death Roles Of Caspase-8mentioning
confidence: 99%
“…In addition to its involvement in apoptosis modulation, c-FLIP plays important roles in controlling proliferation [26] and cardiac hypertrophy after pressure overload [27]. Furthermore, c-FLIP can activate several pro-survival signalling pathways by regulating proteins such as NF-κB, ERK and AKT [28][29][30]. More recently, we demonstrated that c-FLIP −/− mouse embryonic fibroblasts (MEFs) display an enlarged ER structure and strong lipid accumulation [22,31].…”
Section: Introductionmentioning
confidence: 97%